Diagnostic values of clinical diagnostic tests in subacromial impingement syndrome. Issue 1 (1st January 2000) - Çalış, Mustafa; Akgün, Kenan; Birtane, Murat; Karacan, Ilhan; Çalış, Havva; Tüzün, Fikret
Abstract : OBJECTIVE: Subacromial impingement syndrome (SIS) is a frequent cause of shoulder pain. The aim of this study was to investigate the diagnostic values of clinical diagnostic tests, in patients with SIS. METHODS: 72 female, 48 male patients with shoulder pain were included in the study. Five had bilateral shoulder pain, so 125 painful shoulders were evaluated. Details were recorded about the patients' ages and sexes, as well as characteristics of pain and related problems. Detailed physical examination and routine laboratory tests were performed. Conventional radiography and subsequent magnetic resonance imaging of the shoulder region of all patients were performed. Patients were divided into two groups according to the results of subacromial injection test, a reference standard test for SIS. Test positive patients constituted SIS group and test negative patients the non-SIS group. Sensitivity, specificity, accuracy, positive and negative predictive values of some clinical diagnostic tests such as Neer, Hawkins, horizontal adduction, painful arc, drop arm, Yergason and Speed tests for SIS were determined by using 2 × 2 table. RESULTS: The most sensitive diagnostic tests were found to be Hawkins test (92.1%), Neer test (88.7%) and horizontal adduction test (82.0%). Tests with highest specificity were drop arm test (97.2%), Yergason test (86.1%) and painful arc test (80.5%) consecutively. CONCLUSION: The highly sensitive tests seem to have low specificity values and the highly specific ones to have low sensitivity values. Although this finding suggests that these diagnostic tests are insufficient for certain diagnosis, it is suggested they play an important part in clinical evaluation.